Privatizações do subsetor ferroviário de cargas no Brasil: processo e resultados - Lima, Camila Sapetti Bertoche de (2011)
This work aims to study the sub-sector rail freight in Brazil, between pre and postprivatization of the railway companies belonging to the Union, wich occurred in the 1990s. The study plan includes the process and results of privatization and regulation in the other countries, whose railroad has a key role in the transport matrix. Search finally assess whether the outcome of privatization was not satisfactory or for strengthening the sub-sector rail freight in Brazil